1994
DOI: 10.1159/000246813
|View full text |Cite
|
Sign up to set email alerts
|

Various Cytokines Modulate ICAM-1 Shedding on Melanoma- and CTCL-Derived Cell Lines: Inverse Regulation of ICAM-1 Shedding in a Sézary Cell Line by Interferon-γ

Abstract: Background: Since soluble intercellular adhesion molecules 1 (sICAM-1) retain their ability to bind to their ligand, they can interfere in cell-mediated immunosurveillance. Objective: We studied the impact of various cytokines on ICAM-1 release of several tumor cell lines. Methods: Two melanoma cell lines (M19, M26), 1 B lymphoblastoid cell line (Daudi), 1 erythroleukemia cell line (K562), 1 Sézary-cell-derived cell line (SeAx), 1 cell line derived from a mycosis fungoides lesion (MyLa) and normal peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although previous studies have reported sICAM-1 secretion in vitro in several cell lines [14][15][16][17][18] and highly significant sICAM-1 levels in patients' sera in a wide variety of malignancies [18][19][20], the functional role of soluble ICAM-1 is yet to be completely understood. To the best of our knowledge, the present study is the first to show that sICAM-1 has a functional role as an autocrine growth factor for neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have reported sICAM-1 secretion in vitro in several cell lines [14][15][16][17][18] and highly significant sICAM-1 levels in patients' sera in a wide variety of malignancies [18][19][20], the functional role of soluble ICAM-1 is yet to be completely understood. To the best of our knowledge, the present study is the first to show that sICAM-1 has a functional role as an autocrine growth factor for neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 is constitutively expressed on a limited number of tissues, but is induced in a wide variety of normal cells such as vascular endothelial cells, leukocytes, and some epithelial tissues [13]. Soluble ICAM-1 (sICAM-1) secretion in vitro was previously reported in cell lines derived from melanoma, lymphoma, and renal carcinoma [14][15][16][17][18]. In addition, highly significant sICAM-1 levels were reported in the sera from patients suffering from different malignancies [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, shedding of ICAM‐1 may be one of the mechanisms by which neoplastic cells escape immunosurveillance. Shedding of ICAM‐1 is strongly enhanced upon stimulation by IFN‐γ (Dummer et al, 1994).…”
mentioning
confidence: 99%